70.7k views
3 votes
4(2x - 5) -6( ) = 6+9) + (2x - 5)

2 Answers

4 votes

Answer: x=6

Step-by-step explanation:

Step 1: Remove parentheses.

4(2x-5)-6=6+9+2x-54(2x−5)−6=6+9+2x−5

Step 2: Simplify 6+9+2x-56+9+2x−5 to 2x+102x+10.

4(2x-5)-6=2x+104(2x−5)−6=2x+10

Step 3: Expand.

8x-20-6=2x+108x−20−6=2x+10

Step 4: Simplify 8x-20-68x−20−6 to 8x-268x−26.

8x-26=2x+108x−26=2x+10

Step 5: Add 26 to both sides.

8x=2x+10+268x=2x+10+26

Step 6: Simplify 2x+10+262x+10+26 to 2x+362x+36.

8x=2x+368x=2x+36

Step 7: Subtract 2x2x from both sides.

8x-2x=368x−2x=36

Step 8: Simplify 8x-2x8x−2x to 6x.

6x=36

Step 9: Divide both sides by 6.

x= 36/6 as a fraction

Step 10: Simplify \frac{36}{6} to 6.

x= 6x

User Lajos Nagy
by
5.5k points
5 votes


\bold{4(2x - 5) -6 = 6+9) + (2x - 5)}


\bold{4(2x−5)−6=6+9+2x−5}


\bold{4(2x−5)−6=2x+10}


\bold{8x−20−6=2x+10}


\bold{8x=2x+10+26}


\bold{8x=2x+36}


\bold{8x−2x=36}


\bold{6x=36}


\bold{x = \cfrac{36}{6}}


\bold{x = 6}

Note: The Parentheses must be eliminated to then use the law of signs, then we must expand the numbers, then simplify (that is, subtract) Now in the next step is to Add 26 on both sides then we must subtract and then add until we get the result of 6, so that ultimately we can take out a fraction and give us the correct answer, which is
\bold{x=6}

User Oli Crt
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.